Lung volume reduction: advances in COPD - Hopkinson, Nick (Henry Stewart Talks, 2012)
Hyperinflation in COPD, Lung volume reduction surgery (LVRS), Bullectomy, Bronchoscopic techniques including valves, airway bypass, coils, steam and fibrin glue